UPAYA MENINGKATKAN MOTIVASI BELAJAR MELALUI MODEL DISCOVERY LEARNING PADA MATERI GEMPA BUMI DI KELAS VIII SMP YP PGRI DISAMAKAN MAKASSAR BERBANTUAN MEDIA POWERPOINT INTERAKTIF - Zalwa Salima; InayatuDzil Izzati; Agnes Meltipulciana Mendila; Sitti Saenab; Ramlawati Ramlawati; Hasjunika Hasbi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study was a Classroom Action Research (CAR) aimed at improving the learning motivation of eighth-grade students at SMP YP PGRI Disamakan Makassar on the topic of earthquakes through the implementation of the Discovery Learning model assisted by interactive PowerPoint media. The research was conducted in two cycles, each consisting of two meetings. The research instrument used was a learning motivation observation sheet covering aspects of attention, activeness in asking questions, participation in discussions, and students’ learning enthusiasm. The results showed that students’ learning motivation increased gradually from 58.5% in the pre-action stage to 67.4% in Cycle I and increased to 75.5% in Cycle II. In Cycle I, students’ learning motivation began to show positive development; however, some students were still less active and lacked confidence in expressing their opinions. After improvements were made in Cycle II through enhanced media interactivity and more intensive guidance, students became more active in asking questions, participating in discussions, and confidently expressing their opinions in front of the class. Based on these findings, it can be concluded that the implementation of the Discovery Learning model assisted by interactive PowerPoint media was effective in improving students’ learning motivation on earthquake material.